Characterization of solar cell passivating contacts using time-of-flight elastic recoil detection analysis - Shi, Y; Wright, M; Sharpe, MK; McAleese, CD; Polzin, J-I; Niu, X; Zhao, Z; Morris, S; Bonilla Osorio, RS (AIP Publishing, 2023)
The unambiguous detection of hydrogen in solar cell contact structures is critical to understanding passivation and degradation phenomena. Deuterium is often used to depict the distribution of hydrogen more clearly. However, experimental noise and artefacts can hinder the clear identification of species. This work provides a report of time-of-flight elastic recoil detection (ToF-ERD) analysis to identify H/D contents in a thin poly-Si/ SiOx passivating contact. The structure contained a 1.3 nm interfacial SiOx and an n+ doped polySi layer with a partly deuterated SiNx coating. The samples were annealed to release H/D and ToF-ERD was used to detect H/D in monoatomic, singly charged forms, without the detection artefacts associated with conventional secondary ion mass spectroscopy. Chlorine ions were used to recoil surface species which were analyzed to clearly and unambiguously resolve H and D. Depth profiles for the recoiled Si, N, O, D and H atoms were calculated from the energy and velocity information registered after scattering events, which enabled the analysis of the structure of the multilayer stack. Even though the surface roughness and experimental limitations cause visible broadening of the profiles, which can hinder clear detection at the interfacial oxide, the ability to resolve hydrogen-related species makes ToFERD a significant and promising tool for studying the role of hydrogen in the performance and degradation of solar cell passivating contacts.